ANALYZING SPEECH ACT OF LECTURER AND STUDENTS IN CLASS DISCUSSION AT ENGLISH DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH MAKASSAR - Sulviana S.Pd,M.Pd (UKI TORAJA, 2016)
The aims from this research are to find out the kinds of speech acts that mostly appearedin class discussion. The approach employed in this research is qualitative approach. Thetype of this research belongs to discourse analysis (DA). Data collection of this researchwas conducted through (1) video recording, and (2) observation. The data gathered inanalyzing kinds of speech acts, functions of speech acts, and implication of speech acts inclass discussion. The research result shows that of all the kinds of speech acts used bylecturer and students, illocutionary act is the speech act that mostly appeared in classdiscussion.